Modified composite solid electrolyte and preparation method thereof

By using PEO/PVDF-HPF copolymer and silicon carbide in the solid electrolyte of solid state batteries, polymerizing under microwave fields, combining ionic liquid to fill the phase interface gap, the problems of low conductivity and large interface impedance of solid state batteries are solved, and the problem of low conductivity and large interface impedance of solid state batteries is achieved. Higher lithium conduction performance and more uniform heat transfer.

CN119481233APending Publication Date: 2025-02-18BOYAN JIAXIN (BEIJING) TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411500141.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The solid electrolyte ion conductivity of solid state batteries is relatively low and the interface impedance is large, which has poor continuity of organic/inorganic interfaces and uneven heat transfer.

Method used

Using PEO/PVDF-HPF copolymer as the matrix, silicon carbide is added as microwave absorbing material, and film is formed by microwave-assisted under-field polymerization to optimize the distribution structure of inorganic lithium conduction materials, and filling the polymer and inorganic filler by adding ionic liquid. phase interface gap.

Benefits of technology

It improves the uniformity and lithium conduction performance of the composite solid electrolyte, reduces the interface impedance, optimizes heat transfer, and improves the density and processing performance of the electrolyte.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_7
    Figure SMS_7
  • Figure SMS_8
    Figure SMS_8
Patent Text Reader

Abstract

The invention relates to the technical field of solid-state batteries, in particular to a modified composite solid electrolyte and a preparation method thereof. The preparation method comprises the following steps: S1, mixing a PVDF-HPF copolymer, PEO, LTFSI and a solvent to obtain a solution A; s2, mixing an ionic liquid, an inorganic lithium conducting material, silicon carbide and the solution A, and emulsifying to obtain a pouring liquid; s3, pouring the pouring liquid into a mold with a substrate to serve as a solid electrolyte precursor solution; and S4, drying the solid electrolyte precursor solution until the surface is dry, inverting the mold in a microwave field for microwave heating, and then drying the residual solvent to obtain the modified composite solid electrolyte. According to the preparation method, PEO / PVDF-HPF is adopted as a polymer matrix, silicon carbide is added into the polymer matrix, and the polymer matrix is polymerized into a film under microwaves, so that the problem of non-uniform heat transmission in the preparation process can be improved; meanwhile, by adding the ionic liquid, the lithium conductivity of the composite electrolyte can be improved, and the interface impedance is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solid-state batteries, and in particular to a modified composite solid electrolyte and a preparation method thereof. Background Art

[0002] With the rapid development of economy and society, people's demand for energy forms is becoming more and more diversified. As a typical representative of new energy storage, lithium-ion batteries are widely used in consumer electronics, smart industry, aerospace and other fields, and have become the mainstream products in the market. However, liquid lithium-ion batteries are almost close to the limit of materials in terms of energy density, and liquid electrolytes are flammable and have poor safety, which obviously limits the development of lithium-ion batteries. In order to meet the needs of higher energy density and safety, solid-state batteries using solid electrolyte systems have emerged. Solid-state batteries have the characteristics of high safety, high energy density and long cycle life. This is because solid electrolytes do not contain electrolytes, which can effectively avoid problems such as electrolyte leakage and fire, and can operate in a wider temperature and voltage range. However, solid-state battery and electrolyte technology are underdeveloped, and there are problems such as low ion conductivity of solid electrolytes and large interface impedance.

[0003] A Chinese invention patent with publication number CN112864458A discloses a double-layer composite solid electrolyte material, which includes a first layer of polymer and a second layer of polymer stacked together. The first layer and the second layer are mainly composed of a polymer and an inorganic ceramic filler simply mixed with a solvent. Although the compatibility problem of the interface between the electrolyte layer and the electrode layer is alleviated, there is a problem of poor continuity of the organic / inorganic interface. In addition, the multi-layer electrolyte interface will increase the superposition of interface compatibility and impedance problems.

[0004] The Chinese invention patent with publication number CN116646591A discloses a composite solid electrolyte containing a modified inorganic solid electrolyte filler and its preparation and application. The inorganic solid electrolyte filler after dispersion treatment is mixed with a polymer and a lithium salt, and a solvent is added and stirred until completely uniform. Then, the mixture is cast on a mold with a flat surface. After vacuum drying to remove the residual solvent, an organic-inorganic composite solid electrolyte membrane is obtained, which is the target product. Although the problems of particle agglomeration and discontinuous lithium ion transmission path caused by the surface energy difference of the inorganic filler in the current composite solid electrolyte are solved, there is still uneven heat transfer between the polymer and the inorganic filler, and there is a discontinuous phase interface between the inorganic filler and the polymer, which will affect the ion conductivity. Summary of the invention

[0005] In order to explain the technical content, achieved objectives and effects of the present invention in detail, the following is an explanation in conjunction with the implementation modes.

[0006] A method for preparing a modified composite solid electrolyte comprises the following steps: S1: mixing PVDF-HPF copolymer, PEO, LTFSI and solvent to obtain solution A; S2: mixing the ionic liquid, the inorganic lithium conductive material, the silicon carbide and the solution A and emulsifying them to obtain a casting solution; S3: pouring the casting liquid into a mold with a substrate as a solid electrolyte precursor liquid; S4: Dry the solid electrolyte precursor solution until the surface is dry, place the mold upside down in a microwave field for microwave heating, and then dry the remaining solvent to obtain a modified composite solid electrolyte.

[0007] From the above description, it can be seen that the beneficial effects of the present invention are: the overall polymerization and composite film-forming process of the present invention is carried out under a microwave-assisted field. PEO and PVDF-HPF copolymers are used as polymer matrices, and silicon carbide, a microwave absorbing material with high dielectric properties, is added to the polymer matrix. Silicon carbide is used as an internal heating element to strengthen the polymerization process, increase the uniformity of the composite solid electrolyte, improve the problem of uneven heat transfer during the preparation process, optimize the distribution structure of the internal filler (inorganic lithium-conducting material) inside the polymer, and improve the density and processing performance of the composite electrolyte. Silicon carbide also has a strong interaction with the oxygen ions in the PEO / PVDF-HPF matrix, which can promote the rapid migration of lithium ions.

[0008] At the same time, ionic liquids are added to utilize the low miscibility of ionic liquids in polymers to assist in filling the interfacial gap between inorganic fillers such as silicon carbide and inorganic lithium-conductive materials and polymers, thereby improving the lithium-conducting performance of the composite electrolyte and reducing the interface impedance.

[0009] The present invention first mixes the organic phase and the liquid phase, and then adds the ionic liquid, the inorganic lithium conductive material and the silicon carbide to ensure that the materials are mixed evenly.

[0010] The solid electrolyte precursor liquid is dried until the surface is dry and no liquid flows out when the mold is inverted.

[0011] Furthermore, the weight ratio of the PVDF-HPF copolymer, PEO and LTFSI is 30:2-60:10.

[0012] Preferably, the weight ratio of PVDF-HPF copolymer, PEO and LTFSI is 30:10 to 20:10.

[0013] From the above description, it can be seen that increasing the amount of LiTFSI appropriately can improve the conductivity and stability of the battery, but too much LiTFSI may lead to an increase in the internal resistance of the battery; PVDF-HPF has poor conductivity but good mechanical properties, and the ether oxygen functional groups in PEO are easy to coordinate with Li, but the mechanical properties are poor. Therefore, PVDF-HPF copolymer and PEO are mixed in a certain proportion to prepare an electrolyte with good electrical and mechanical properties.

[0014] Furthermore, the solvent includes DMF (N,N-dimethylformamide) and acetonitrile in a volume ratio of 1:2-4.

[0015] Preferably, the solvent comprises DMF (N,N-dimethylformamide) and acetonitrile in a volume ratio of 1:3.

[0016] From the above description, it can be seen that a small amount of DMF solvent molecules and Li + It has stronger coordination, but DMF alone is difficult to remove as a solvent. At the same time, excessive DMF content will cause serious interfacial reaction with lithium metal; therefore, the ratio of DMF to acetonitrile is controlled to be 1:2~4.

[0017] Furthermore, the ratio of LTFSI to solvent is 5:9~21.

[0018] Furthermore, the stirring rate during mixing in S1 is 550-650 rpm, and the time is 18-24 h.

[0019] Furthermore, the mass of the ionic liquid is 0.4-0.6% of the mass of solution A.

[0020] From the above description, it can be seen that adding too much ionic liquid will lead to waste of raw materials, while adding too little will not be able to fill the interfacial gap between the inorganic material and the polymer well and reduce the interfacial impedance; therefore, the mass of the ionic liquid is controlled to be 0.4~0.6% of the mass of solution A.

[0021] Furthermore, the mass of the inorganic lithium conductive material is 1.8-2.2% of the mass of solution A.

[0022] From the above description, it can be seen that if too much inorganic lithium conductive material is added, the toughness of the electrolyte will deteriorate and the interface impedance will increase, while if too little is added, the conductivity of the electrolyte will be relatively reduced; therefore, the mass of the inorganic lithium conductive material is controlled to be 1.8~2.2% of the mass of solution A.

[0023] Furthermore, the mass of silicon carbide is 0.8-1.2% of the mass of solution A.

[0024] From the above description, it can be seen that the main function of silicon carbide is to solve the heat transfer between organic and inorganic substances. Adding too much silicon carbide will cause waste of raw materials and increase costs. Adding too little will lead to uneven heat dispersion and the interface problem between the two substances cannot be well solved. Therefore, the mass of silicon carbide is controlled to be 0.8~1.2% of the mass of solution A.

[0025] Further, the ionic liquid includes PP13-TFSI (N-methyl-N-propylpiperidinium di(trifluoromethylsulfonyl)imide) or PYR14FSI (N-methyl-N-butylpyrrolidine di(fluorinated amido)imide).

[0026] Preferably, the ionic liquid is PP13-TFSI.

[0027] From the above description, it can be seen that PP13-TFSI ionic liquid is easier to diffuse on the organic-inorganic interface, and has high conductivity and good flow properties.

[0028] Furthermore, the inorganic lithium conductive material includes LLTO (lithium lanthanum titanium oxide) or LLZO (lithium lanthanum zirconium oxide).

[0029] Furthermore, the thickness of the modified composite solid electrolyte is 25-180 μm.

[0030] Furthermore, the drying temperature is 45-60°C.

[0031] From the above description, it can be seen that using a lower drying temperature can prevent the interface from cracking due to uneven drying of the solution during the drying process.

[0032] Furthermore, the microwave power of microwave heating is 150-200 W, and the time is 10-30 s.

[0033] From the above description, it can be seen that if the microwave heating power and time are too high, the electrolyte interface will crack, while too low a frequency and time will make the interface unstable and the drying not thorough enough; therefore, the microwave power of microwave heating is controlled to be 150~200W and the time is 10~30s.

[0034] Another technical solution adopted by the present invention is: a modified composite solid electrolyte is prepared by the preparation method of the modified composite solid electrolyte.

[0035] Embodiment 1 of the present invention is: a method for preparing a modified composite solid electrolyte, the steps are as follows: S1: 30 g PVDF-HPF copolymer, 30 g PEO, 10 g LTFSI and 40 mL solvent were magnetically stirred at a rate of 600 rpm for 20 h to obtain solution A; the solvent included DMF and acetonitrile in a volume ratio of 1:3.

[0036] S2: Add PP13-TFSI, LLTO and silicon carbide to solution A, and perform high-speed shear emulsification and dispersion at 2000 rpm for 15 minutes to obtain a casting solution, which is allowed to stand to discharge bubbles for standby use; the mass of the ionic liquid is 0.5% of the mass of solution A, the mass of the inorganic lithium conductive material is 2.0% of the mass of solution A, and the mass of silicon carbide is 1.0% of the mass of solution A.

[0037] S3: The casting liquid is cast into a polytetrafluoroethylene mold of a release film substrate using a casting method as a solid electrolyte precursor liquid.

[0038] S4: The solid electrolyte precursor liquid in the polytetrafluoroethylene mold was dried at 50°C until the surface was dry, the mold was inverted and placed in a microwave field, heated at a microwave power of 160 W for 20 s, and then the remaining solvent was dried to obtain a modified composite solid electrolyte with a thickness of 100 μm.

[0039] Embodiment 2 of the present invention is: a method for preparing a modified composite solid electrolyte, the steps are as follows: S1: 30 g of PVDF-HPF copolymer, 2 g of PEO, 10 g of LTFSI and 30 mL of solvent were magnetically stirred at a rate of 550 rpm for 18 h to obtain solution A; the solvent included DMF and acetonitrile in a volume ratio of 1:2.

[0040] S2: PYR14FSI, LLZO and silicon carbide are added to solution A, and high-speed shear emulsification and dispersion are performed at 2000 rpm for 15 minutes to obtain a casting liquid, which is allowed to stand to discharge bubbles for standby use; the mass of the ionic liquid is 0.4% of the mass of solution A, the mass of the inorganic lithium-conducting material is 1.8% of the mass of solution A, and the mass of silicon carbide is 0.8% of the mass of solution A.

[0041] S3: The casting liquid is cast into a polytetrafluoroethylene mold of a release film substrate using a casting method as a solid electrolyte precursor liquid.

[0042] S4: The solid electrolyte precursor liquid in the polytetrafluoroethylene mold was dried at 45°C until the surface was dry, the mold was inverted and placed in a microwave field, heated at a microwave power of 150 W for 30 s, and then the remaining solvent was dried to obtain a modified composite solid electrolyte with a thickness of 25 μm.

[0043] Embodiment 3 of the present invention is: a method for preparing a modified composite solid electrolyte, the steps are as follows: S1: 30 g PVDF-HPF copolymer, 60 g PEO, 10 g LTFSI and 50 mL solvent were magnetically stirred at a rate of 650 rpm for 24 h to obtain solution A; the solvent included DMF and acetonitrile in a volume ratio of 1:4.

[0044] S2: Add PP13-TFSI, LLTO and silicon carbide to solution A, and perform high-speed shear emulsification and dispersion at 2000 rpm for 15 minutes to obtain a casting solution, which is allowed to stand to discharge bubbles for standby use; the mass of the ionic liquid is 0.6% of the mass of solution A, the mass of the inorganic lithium conductive material is 2.2% of the mass of solution A, and the mass of silicon carbide is 1.2% of the mass of solution A.

[0045] S3: The casting liquid is cast into a polytetrafluoroethylene mold of a release film substrate using a casting method as a solid electrolyte precursor liquid.

[0046] S4: The solid electrolyte precursor liquid in the polytetrafluoroethylene mold was dried at 60°C until the surface was dry, the mold was inverted and placed in a microwave field, heated at a microwave power of 200 W for 10 s, and then the remaining solvent was dried to obtain a modified composite solid electrolyte with a thickness of 180 μm.

[0047] Example 4 of the present invention is: a modified composite solid electrolyte prepared by the preparation method of Example 1.

[0048] Comparative Example 1 of the present invention is: The only difference between Comparative Example 1 and Example 1 is that silicon carbide is not added.

[0049] Comparative Example 2 of the present invention is: The only difference between Comparative Example 2 and Example 1 is that PP13-TFSI is not added.

[0050] The modified composite solid electrolytes prepared in Example 1, Comparative Example 1 and Comparative Example 2 were subjected to the following tests.

[0051] 1. The ion migration number of the modified composite solid electrolyte prepared in Example 1 and Comparative Example 1 was detected by the following method: a symmetrical Li|SSEs|Li battery was assembled, and the lithium ion migration number (tLi+) of the sample film was measured by combining electrochemical impedance spectroscopy (EIS) and direct current (DC) polarization method, which can be calculated according to the following formula:

[0052] in, represents the applied polarization voltage (unit: V), which is 10 mV. and represent the initial current and battery interface resistance respectively, and Respectively represent the current and battery interface resistance in steady state; the test results are shown in Table 1 Table 1

[0053] As can be seen from Table 1, the addition of silicon carbide can optimize the distribution structure of inorganic lithium-conducting materials inside the polymer, increase the uniformity of the composite solid electrolyte, avoid excessive local current density, and thus increase the lithium ion migration number.

[0054] 2. The ionic conductivity of the modified composite solid electrolytes of Example 1, Comparative Example 1 and Comparative Example 2 was tested by assembling a symmetrical stainless steel (SS) | SSEs | SS battery and measuring the ionic conductivity of the electrolyte by electrochemical impedance spectroscopy (EIS). The open circuit voltage was used and the test frequency range was 0.01 Hz to 1000 kHz. The conductivity value can be calculated by the following formula:

[0055] Where σ represents the ionic conductivity of the sample membrane, unit: S cm -1 ; R, l and S represent the bulk resistance (unit: Ω), thickness (unit: cm) and area (unit: cm) of the measured electrolyte membrane respectively. 2 ). The test results are shown in Table 2.

[0056] Table 2

[0057] It can be seen from Table 2 that adding silicon carbide or ionic liquid can reduce the impedance and improve the lithium conductivity of the composite electrolyte.

[0058] In summary, the modified composite solid electrolyte and the preparation method thereof provided by the present invention have the following advantages: 1. Silicon carbide is added to the PEO / PVDF-HPF matrix. Silicon carbide has a strong interaction with the oxygen ions in the PEO / PVDF-HPF matrix, which can promote the rapid migration of lithium ions. At the same time, with the microwave-assisted field polymerization film formation, silicon carbide acts as an internal heating element to strengthen the polymerization process, improve the problem of uneven heat transfer in the preparation process, and optimize the distribution structure of internal fillers in the polymer.

[0059] 2. Inorganic fillers are added to the PEO / PVDF-HPF matrix to form a model similar to filling the pores inside a sponge with sand, and ionic liquids are added; the low miscibility of ionic liquids in polymers is utilized to force them to be positioned at the phase interface, assisting in filling the phase interface gap between the inorganic fillers and the polymer, acting as a bridge for lithium ion transmission, thereby improving the lithium conductivity of the composite solid electrolyte and reducing the interfacial impedance.

[0060] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent transformations made using the specification of the present invention, or directly or indirectly applied in related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A method for preparing a modified composite solid electrolyte, characterized in that: The following steps are involved: S1: mixing PVDF-HPF copolymer, PEO, LTFSI and solvent to obtain solution A; S2: mixing the ionic liquid, the inorganic lithium conductive material, the silicon carbide and the solution A and emulsifying them to obtain a casting solution; S3: pouring the casting liquid into a mold with a substrate as a solid electrolyte precursor liquid; S4: Dry the solid electrolyte precursor solution until the surface is dry, place the mold upside down in a microwave field for microwave heating, and then dry the remaining solvent to obtain a modified composite solid electrolyte.

2. The method for preparing the modified composite solid electrolyte according to claim 1, characterized in that: The weight ratio of the PVDF-HPF copolymer, PEO and LTFSI is 30:2-60:

10.

3. The method for preparing the modified composite solid electrolyte according to claim 1, characterized in that: The solvent comprises DMF and acetonitrile in a volume ratio of 1:2-4.

4. The method for preparing the modified composite solid electrolyte according to claim 1, characterized in that: The stirring rate during mixing in S1 is 550-650 rpm, and the mixing time is 18-24 hours.

5. The method for preparing the modified composite solid electrolyte according to claim 1, characterized in that: The mass of the ionic liquid is 0.4-0.6% of the mass of solution A.

6. The method for preparing the modified composite solid electrolyte according to claim 1, characterized in that: The mass of the inorganic lithium conductive material is 1.8-2.2% of the mass of solution A.

7. The method for preparing a modified composite solid electrolyte according to claim 1, characterized in that: The mass of the silicon carbide is 0.8-1.2% of the mass of solution A.

8. The method for preparing the modified composite solid electrolyte according to claim 1, characterized in that: The thickness of the modified composite solid electrolyte is 25-180 μm.

9. The method for preparing a modified composite solid electrolyte according to claim 1, characterized in that: The microwave power of the microwave heating is 150-200W, and the time is 10-30s.

10. A modified composite solid electrolyte prepared by the method for preparing a modified composite solid electrolyte according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Double-layer composite solid electrolyte material and preparation method and application thereof

    CN112864458A

  • Composite solid electrolyte containing modified inorganic solid electrolyte filler and preparation and application thereof

    CN116646591A

  • Organogel polymer electrolytic solution, preparation method, application, sodium-based dual-ion battery and preparation method thereof

    CN109638344A

  • Solid electrolyte and preparation method thereof and lithium ion battery

    CN111900468A

  • Composite solid electrolyte, composite solid electrolyte sheet, preparation method of composite solid electrolyte sheet and chemical battery

    CN117219841A